Effect of Nanocomposite Structures on Fracture Behavior of Epoxy-Clay Nanocomposites Prepared by Different Dispersion Methods. (2nd June 2014) - Bashar, Mohammad; Mertiny, Pierre; Sundararaj, Uttandaraman
Abstract : The effects of organic modifier and processing method on morphology and mechanical properties of epoxy-clay nanocomposites were investigated. In this study, the preparation of nanocomposites by exfoliation-adsorption method involved an ultrasonic mixing procedure, and mechanical blending was used for in situ intercalative polymerization. The microstructure study revealed that the organoclay, which was ultrasonically mixed with the epoxy, partially exfoliated and intercalated. In contrast, organoclay remained in phase-separated and flocculated state after the mechanical blending process. Tensile stiffness increased significantly for the nanocomposite prepared by ultrasonic dispersion method through realizing the reinforcing potential of exfoliated silicate layers. Nanocomposites with exfoliated and intercalated nanoclay morphology were ineffective in enhancing the fracture toughness whereas nanocomposites with phase-separated and flocculated morphology have improved crack resistance predominantly by crack deflecting and pinning mechanisms.